2022
DOI: 10.3389/fmicb.2022.826571
|View full text |Cite
|
Sign up to set email alerts
|

Application of Arbuscular Mycorrhizal Fungi in Vineyards: Water and Biotic Stress Under a Climate Change Scenario: New Challenge for Chilean Grapevine Crop

Abstract: The crop Vitis vinifera (L.) is of great economic importance as Chile is one of the main wine-producing countries, reaching a vineyard area of 145,000 ha. This vine crop is usually very sensitive to local condition changes and agronomic practices; therefore, strategies to counteract the expected future decrease in water level for agricultural irrigation, temperature increase, extreme water stress (abiotic stress), as well as increase in pathogenic diseases (biotic stress) related to climate change will be of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Studies carried out in recent years have suggested that arbuscular mycorrhizal fungi such as Diversispora can provide key ecosystem services to host plants Crop diversity enriches arbuscular mycorrhizal fungal communities in an intensive agricultural landscape, Agroecology: the key role of arbuscular mycorrhizas in ecosystem services. They not only enhance water uptake and the absorption of nutrients such as P and N but also contribute to bioprotection against pathogens in viticulture 35 . The family Cordycipitaceae represented signi cant changes in the seed fungal microbiota, which was characteristic of must cluster 2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in recent years have suggested that arbuscular mycorrhizal fungi such as Diversispora can provide key ecosystem services to host plants Crop diversity enriches arbuscular mycorrhizal fungal communities in an intensive agricultural landscape, Agroecology: the key role of arbuscular mycorrhizas in ecosystem services. They not only enhance water uptake and the absorption of nutrients such as P and N but also contribute to bioprotection against pathogens in viticulture 35 . The family Cordycipitaceae represented signi cant changes in the seed fungal microbiota, which was characteristic of must cluster 2.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on grapevine have shown that AMF application can be a reliable approach to vine resilience in wine-producing regions ( Malhi et al., 2021 ; Aguilera et al., 2022 ). Our experiment corroborated the previous findings, implying a different modulation of photosynthetic energy allocation, physiological activity, and, consequently, fruit biochemistry of grapevine plants in a hyper-arid growing season, following the application of seven mycorrhizal-based commercial products.…”
Section: Discussionmentioning
confidence: 99%
“…Such a root system has the potential to penetrate the lower soil horizons thereby substantially affecting the soil microbial and enzymatic properties. Additionally, some authors have suggested that the arbuscular mycorrhizal fungi (AMF), which are associated with grape roots enhance water uptake and the absorption of nutrients such as phosphorus and nitrogen, which are important for improving the nutritional status of the grapevine [75]. The results of our study have indicated that in the 8-year-long period of viticulture, a significantly higher root mass (relative to the WW profiles) might account for the increase in the soil microbial content and certain enzyme activities.…”
Section: Land Use and Plant Cover As The Main Factors That Affect The...mentioning
confidence: 99%